2022
DOI: 10.3390/ijerph19116787
|View full text |Cite
|
Sign up to set email alerts
|

Harmonization of Human Biomonitoring Studies in Europe: Characteristics of the HBM4EU-Aligned Studies Participants

Abstract: Human biomonitoring has become a pivotal tool for supporting chemicals’ policies. It provides information on real-life human exposures and is increasingly used to prioritize chemicals of health concern and to evaluate the success of chemical policies. Europe has launched the ambitious REACH program in 2007 to improve the protection of human health and the environment. In October 2020 the EU commission published its new chemicals strategy for sustainability towards a toxic-free environment. The European Parliam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 54 publications
0
37
0
1
Order By: Relevance
“…The aim of this initiative was to harmonise human biomonitoring in Europe to support policy making ( Ganzleben et al, 2017 ). Design and general characteristics of the HBM4EU aligned studies was described elsewhere ( Gilles et al, 2021 , 2022 ). Briefly, the HBM4EU aligned studies collected comparable exposure data, questionnaire data and data on health outcomes across the European studies.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this initiative was to harmonise human biomonitoring in Europe to support policy making ( Ganzleben et al, 2017 ). Design and general characteristics of the HBM4EU aligned studies was described elsewhere ( Gilles et al, 2021 , 2022 ). Briefly, the HBM4EU aligned studies collected comparable exposure data, questionnaire data and data on health outcomes across the European studies.…”
Section: Methodsmentioning
confidence: 99%
“… COUNTRY (COUNTRY CODE) a STUDY TOTAL PARTICIPANTS FEMALE MALE AGE RANGE (YEARS) SAMPLING YEARS COMPOUNDS ANALYZED STUDY REFERENCE, WHERE AVAILABLE BELGIUM (BE) 3xG 133 67 66 7–8 2019–2020 BDCIPP, DPHP, BCIPP Govarts et al (2020) CZECH REPUBLIC (CZ) CELSPAC 195 106 89 11–12 2019 BCEP, BCIPP. BDCIPP, DPHP Not available GERMANY (DE) GerES V 300 150 150 6–12 2015–2016 BCEP, BCIPP, BDCIPP, DPHP European Commission (2021a) DENMARK (DK) OCC 291 130 161 7 2018–2019 BDCIPP, DPHP, BCIPP Kyhl et al (2015) GREECE (EL) CROME 55 31 24 6–11 2020–2021 PBDE-47, -153, −209, DP, HBCDD, DBDPE (EnvE Lab, 2022 ; Gilles et al, 2022 ) FRANCE (FR) ESTEBAN 413 191 222 …”
Section: Methodsmentioning
confidence: 99%
“…All participating studies in the HBM4EU survey adhered to national and European ethics regulations ( Gilles et al, 2021 ). The ethical information of all participating studies is provided in Table S2 ( Gilles et al, 2022 ). Three laboratories analyzed brominated FRs and DPs using gas chromatography-tandem mass spectrometry (GC-MS/MS).…”
Section: Methodsmentioning
confidence: 99%
“…Data on Gly and AMPA in urine of adults were obtained in HBM4EU-aligned studies from Germany (UBA ESB; 2015–2020), Switzerland (Swiss TPH HBM4EU study; 2020), France (ESTEBAN; 2014–2016) and Iceland (DIET-HBM; 2019–2020). The study designs are described in Gilles et al (2021) [ 9 ] and characteristics of study participants and ethics can be found in Gilles et al (2022) [ 10 ]. The Swiss HBM4EU study, DIET-HBM and ESTEBAN are nationally representative campaigns.…”
Section: Methodsmentioning
confidence: 99%